THE CONCEPT OF TOLERANCE AND RULES OF MEDIATION IN PEDAGOGICAL CONFLICTOLOGY (Conferencea, 2022)
This article provides detailed information on pedagogical conflict and its causes, the concept of tolerance and its manifestations in society, meditation and its rules, scholars who have studied pedagogical conflictology and their views on pedagogical conflictology.